2006
DOI: 10.1002/ijc.21678
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intake and the risk of stomach and oesophagus adenocarcinoma in the European Prospective Investigation into Cancer and Nutrition (EPIC–EURGAST)

Abstract: It is considered that fruit and vegetable (F&V) protect against oesophagus and gastric cancer (GC). However, 2 recent meta‐analyses suggest that the strength of association on GC seems to be weaker for vegetables than for fruit and weaker in cohort than in case‐control studies. No evidence exists from cohort studies about adenocarcinoma of oesophagus (ACO). In 521,457 men and women participating in the EPIC cohort in 10 European countries, information of diet and lifestyle was collected at baseline. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
228
4
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(249 citation statements)
references
References 30 publications
11
228
4
6
Order By: Relevance
“…Primary prevention of stomach cancer by dietary means is feasible by encouraging high-risk populations to decrease consumption of cured meats and salt preserved foods, and increase the consumption of vegetables and fruit. [42][43][44][45][46][47] Prevention may also be feasible through eradication of H. pylori infection, particularly in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Primary prevention of stomach cancer by dietary means is feasible by encouraging high-risk populations to decrease consumption of cured meats and salt preserved foods, and increase the consumption of vegetables and fruit. [42][43][44][45][46][47] Prevention may also be feasible through eradication of H. pylori infection, particularly in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing fruit and vegetable consumption continues to be considered a factor capable of lowering the risk of developing gastric cancer, although recent prospective studies have not been able to confirm this effect (81,167) . Neither was vitamin supplementation in the diet also able to reduce the gastric cancer risk (6) .…”
Section: Statement 11mentioning
confidence: 99%
“…The intake of some fruits and vegetables has been suggested to be inversely associated with the risk of GCs (World Cancer Research Fund, 1997;Riboli and Norat, 2003;Gonzalez et al, 2006), an effect that may be owing to the various carotenoids and antioxidant vitamins present in these foods (Donaldson, 2004). Several case -control studies have shown strong inverse associations between GC risk and higher consumption of some of these nutrients (Buiatti et al, 1990(Buiatti et al, , 1991Gonzalez et al, 1994;Hansson et al, 1994;Ekstrom et al, 2000).…”
mentioning
confidence: 99%